MODELLING CHANGES IN THE MASS BALANCE OF GLACIERS OF THE NORTHERN HEMISPHERE FOR A TRANSIENT 2 X CO2 SCENARIO - Schneeberger C.; Blatter H.; Wild M.; Abe-Ouchi A. (My University, 2003)
A climate forecast provided by a General Circulation Model (GCM), a glacier mass balance model and a glacier flow model is applied to a sample of 11 small glaciers. Another sample of six glaciers and six large, heavily glacierized areas in the arctic were modelled using only the climate forecast and the glacier mass balance model.The climate forecast of two different GCM's with identical experimental setup takes into account a gradual increase in atmospheric content of CO2 and other greenhouse gases to a doubled CO2 equivalent in 2050 corresponding to the IPCC Scenario IS92a. The differences between the two GCM's are significant for the future development of the glacierization of arctic areas.The glacier mass balance model consists of a temperature index melt model, which uses potential direct clear sky radiation to obtain a better spatial and temporal resolution, combined with imposed snow precipitation. Static mass balance sensitivities span −0.2 to −1.5 mwe a−1 °C, the higher and lower sensitivities apply for glaciers in more maritime and continental climates, respectively. All of the modelled glaciers and glacierized regions show a strong decrease in the net mass balance. Temperature changes dominate the effect of snow precipitation on the net mass balance. A temperature increase results in substantial increase in melt especially through the extension of the melt season in spring and fall. The mass balance projections for the sample of 11 glaciers are then used in a glacier flow model to simulate the dynamic reaction of the glacier to the changing climatic conditions. An iteration procedure accounts for possible feedback of changes in the glacier area and the ice surface elevation to the projected mass balance.For the modelled glaciers, an average volume loss of 60% until 2050 is predicted. Without the above iteration and assuming a constant glacier area, the volume change is overestimated by about 20%. A comparison with the climate predictions of the two different GCMs shows only a difference of about 10% in the mass loss obtained by flow modelling of four glaciers.
Keywords: Glacier; Climate change; Mass balance; Ice volume